The contribution of the Emeishan large igneous province to the strontium isotope evolution of the Capitanian seawater. Issue 15 (13th October 2019) - Huang, Hu; Hou, Mingcai; Qing, Hairuo; Zhou, Lian; Yang, Jianghai; Du, Yuansheng; Tian, Jingchun; Ni, Shijun; Xiong, Fuhao
ABSTRACT: The 87 Sr/ 86 Sr minimum of the Capitanian seawater is one of the most significant features in the Phanerozoic seawater 87 Sr/ 86 Sr history. In order to assess possible contribution of the Emeishan large igneous provinces (LIPs) to strontium isotope evolution of the Capitanian seawater, 87 Sr/ 86 Sr ratios were measured from the Capitanian limestones which are locally interlayered with the Emeishan basalts. The limestones underlying the Emeishan basalts have high 87 Sr/ 86 Sr ratios (0.7070–0.7074). However, extremely low 87 Sr/ 86 Sr ratios (0.7068–0.7070) were identified in the late Capitanian Jinogondolella prexuanhanensis – J. xuanhanensis zones, which correspond to the eruption time of the Emeishan LIP. The temporal coincidence of these two phenomena supports the idea of a potential linkage between Capitanian 87 Sr/ 86 Sr minimum and eruption of this igneous province. The strong submarine hydrothermal activity and erosion of the Emeishan LIP could have released large amounts of non-radiogenic Sr to the oceans and play an important role in strontium isotope evolution of the seawater. Graphical Abstract: